Homology Modeling and Molecular Dynamics Study of C-Terminal Catalytic Domain of Human Protein Kinase D1 - Shan Zhao, Yong; Xu, Yang; Wang, Kun; Zeng, Hong; Wang, Jian; Cheng Mao, Sheng; Hai Zhang, Jing (Asian Journal of Chemistry, 2012)
The three-dimensional (3D) model of the C-terminal catalytic domain of human protein kinase D1 (hPKD1c) was constructed based on the crystal structure of the protein kinase Chk2 (PDB code 2CN5) in complex with ADP using Modeller9v2 program. With the aid of molecular mechanics and molecular dynamics method, the last model was obtained and further assessed by Procheck, Prosa2003 and Profile-3D, which confirms that the refined model is reliable. Furthermore, the docking results of Gö6976 1 and its structural analogues into the active site of hPKD1c indicate that 2,6-naphthyridine 13c is a more preferred ligand than others, which is in good agreement with the experimental results. From the docking studies, we also suggest that Ser12, Lys82, Leu83, His84, Asp86, Glu89 and Leu134 in the hPKD1c are important determinant residues in binding as they have strong electrostatic interactions with the ligand.